Composition coating for metal surface and preparation method thereof
By using precured epoxy resin, PU-PI polymer and magnetic corrosion-inhibiting particles composition coatings on metal surfaces, the problems of insufficient adhesion and unstable corrosion resistance in harsh environments are solved, and high adhesion and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411918071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing metal surface topcoat coatings lack adhesion and are prone to peel off in humid or dusty environments, making them difficult to meet high-strength operation needs, and the corrosion resistance is unstable.
A composition coating is used, which includes precured epoxy resin, PU-PI polymer and magnetic corrosion inhibitor particles, and the corrosion-suppressing substance is released through the tight connection of the precured epoxy resin to the PU-PI polymer and the directional migration of the magnetic corrosion inhibitor particles, thereby enhancing the adhesion and corrosion resistance of the coating.
It significantly improves the adhesion and peel resistance of the topcoat coating, and significantly reduces the corrosion level of metal surfaces in harsh environments and extends the service life of the metal surface.
Smart Images

Figure BDA0005207274330000101 
Figure BDA0005207274330000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating compositions, and in particular to a coating composition for metal surfaces and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization and the continuous improvement of technology, the demand for metal surface treatment is also increasing. Metal surface treatment is usually to improve its surface properties, especially in improving the corrosion resistance of metals. The traditional metal surface treatment process is relatively cumbersome and requires multiple steps to complete. The most common one is to use anti-corrosion coating to achieve the protection function.
[0003] The metal surface treatment method widely used in the industry currently mainly involves spraying a primer to enhance adhesion before applying a topcoat. Although this method can ensure good adhesion and significant protection, it also brings a series of problems, such as adding additional operating steps, making the overall process lengthy and increasing the total cost. Therefore, the researchers proposed whether it is possible to remove the primer and only use the topcoat to save process market and consumption costs.
[0004] However, existing topcoats generally have problems such as insufficient adhesion and easy peeling, especially in humid or dusty environments, where the durability of the coating is significantly reduced. Although some coatings claiming to have self-adhesive properties have appeared on the market, most of them are still difficult to completely replace the role of primers in actual applications, especially under high humidity and extreme temperature conditions. The coating performance is unstable and it is difficult to meet the needs of high-intensity operations, and the anti-corrosion effect of the metal surface is greatly reduced. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a composition coating for metal surface and a preparation method thereof.
[0006] In the first aspect, the present application provides a composition coating for metal surfaces and a preparation method thereof, wherein the raw materials used include the following components in parts by weight: 110-120 parts of precured epoxy resin; 20-25 parts of PU-PI polymer; 0.5-1.5 parts of magnetic corrosion inhibition particles; and 25-30 parts of organic solvent.
[0007] Preferably, by weight, the amount of the precured epoxy resin is 115 parts, the amount of the PU-PI polymer is 23 parts, the amount of the magnetic corrosion-inhibiting particles is 1.0 parts, and the amount of the organic solvent is 27 parts.
[0008] The preparation method of the precured epoxy resin is as follows: the epoxy resin is mixed with a curing agent, and precured for 3 minutes under certain temperature and humidity conditions to obtain the precured epoxy resin.
[0009] The preparation method of the PU-PI polymer is as follows: after heating polybutylene glycol until it is melted, hexamethylene diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred to obtain an HDI-PTMEG prepolymer; after cooling to room temperature, anhydrous N,N-dimethylacetamide and isophthalic acid dihydrazide are added, and stirring is continued at room temperature for chain extension reaction to obtain a PU solution; diaminodiphenyl ether and anhydrous N,N-dimethylacetamide are mixed, stirred under a nitrogen atmosphere, and then a hexafluorodianhydride-anhydrous N,N-dimethylacetamide solution is added to obtain a PI solution; after heating the PU solution, an equal volume of the PI solution is added thereto to react and obtain a PU-PI polymer.
[0010] By adopting the above technical scheme, the present application first utilizes a curing agent to pre-cure the epoxy resin under certain conditions, thereby increasing the number of active sites on the epoxy resin molecules, making it easier to combine with a PU-PI polymer having both a soft segment and a rigid segment, thereby adding the PU-PI polymer to the system, and utilizing the mechanical stability and strong interfacial adhesion of the PU-PI polymer to improve the adhesion of the composite coating to the metal surface and its own corrosion resistance. The system is also tightly connected internally, so that the final topcoat coating can be durably bonded to the metal surface and has a higher density.
[0011] In addition, the present application adds magnetic corrosion-inhibiting particles, which can be evenly dispersed in the system without large-area agglomeration. During the spraying and curing process of the composition coating, the magnetic corrosion-inhibiting particles are affected by the magnetic field on the metal surface, and will migrate in a directed manner under the magnetic field and be enriched in the area near the metal surface. At this time, the MBT in the magnetic corrosion-inhibiting particles can move along the shortest path when the metal surface is corroded and quickly form a passivation layer at the corrosion site, thereby providing good protection for the metal surface.
[0012] In summary, in the composition coating of the present application, the precured epoxy resin and the PU-PI polymer can be tightly linked in the system and form a strong interface bonding with the metal surface, which greatly improves the adhesion and peeling resistance of the composition coating. The magnetic corrosion-inhibiting particles can further enhance the corrosion resistance of the composition coating by virtue of their own ability to migrate in a directed manner with the magnetic field and release corrosion-inhibiting substances. Therefore, the composition coating of the present application protects the metal surface from the two aspects of improving the adhesion effect and the anti-corrosion effect of the topcoat coating, thereby significantly reducing the degree of corrosion in harsh environments and greatly extending the service life of the metal surface.
[0013] Preferably, the preparation method of the magnetic corrosion-inhibiting particles comprises the following steps: I. mixing hexadecyltrimethylammonium bromide, Fe3O4 nanoparticles, ethylene glycol and tetraethyl orthosilicate, reacting to obtain a precipitate, calcining the precipitate, washing, and drying to obtain magnetic particles; II. mixing 2-mercaptobenzothiazole and magnetic particles in a weight ratio of (3-5):100, adsorbing under reduced pressure, centrifuging, washing, and drying to obtain magnetic corrosion-inhibiting particles.
[0014] By adopting the above-mentioned technical scheme, the present application uses Fe3O4 nanoparticles and tetraethyl orthosilicate to prepare magnetic particles with a certain hollow structure, and then uses a low-pressure infiltration method to prepare magnetic corrosion-inhibiting particles loaded with 2-mercaptobenzothiazole with a corrosion-inhibiting effect on the magnetic particles. The magnetic corrosion-inhibiting particles can migrate in a direction with the magnetic field and release corrosion-inhibiting substances, thereby improving the corrosion resistance of the composite coating.
[0015] Preferably, the Fe3O4 nanoparticles in step I are also subjected to MoS2 loading treatment, specifically: MoS2 and Fe3O4 nanoparticles in a weight ratio of (0.4-1):1 are dispersed in DMF, stirred for reaction, filtered, washed, and dried to obtain MoS2-loaded Fe3O4 nanoparticles.
[0016] By adopting the above-mentioned technical scheme, the present application loads MoS2 on Fe3O4 nanoparticles, and the two can form covalent bonds under silane connection, which not only enhances the binding force between the magnetic corrosion inhibition particles and other components, but also increases the cross-linking density inside the topcoat coating, and reduces the possibility of corrosive substances diffusing into the topcoat coating / metal surface, thereby providing good corrosion protection for the metal surface. At the same time, it can also rely on the high mechanical stability of Fe3O4 nanoparticles and MoS2 to further enhance the wear resistance of the topcoat coating.
[0017] The present application controls the weight ratio of MoS2 and Fe3O4 nanoparticles, improves the corrosion inhibition effect of the magnetic corrosion inhibition particles and the balance between the intuitive anti-corrosion effect and the anti-stripping effect on the topcoat coating. If the amount of MoS2 is too large, the surface density of the Fe3O4 nanoparticles will be excessively increased, which is not conducive to the wetting and loading of 2-mercaptobenzothiazole and will reduce the ability of the magnetic corrosion inhibition particles to form a passivation layer; if the amount of MoS2 is too small, it will not be able to effectively improve the wear resistance and intuitive anti-corrosion ability of the topcoat coating.
[0018] The present application also controls the weight ratio between 2-mercaptobenzothiazole and the magnetic particles, and improves the corrosion inhibition effect of the magnetic corrosion inhibition particles as much as possible without incurring additional costs. If the amount of 2-mercaptobenzothiazole added is insufficient, the corrosion inhibition effect cannot be effectively improved; but if the amount of 2-mercaptobenzothiazole added is too large, the corrosion inhibition effect of the magnetic corrosion inhibition particles will not be further improved.
[0019] Preferably, the weight ratio of the MoS2 to Fe3O4 nanoparticles is 0.6:1.
[0020] By adopting the above technical scheme, the present application strictly controls the weight ratio of MoS2 and Fe3O4 nanoparticles to 0.6:1, so that the corrosion inhibition effect of the magnetic corrosion inhibition particles and the balance between their intuitive anti-corrosion effect and wear resistance effect on the topcoat coating are optimized. Experimental data show that at this time, the corrosion potential of the topcoat coating is -0.043V and the friction coefficient is 0.342.
[0021] Preferably, in step II, the weight ratio of 2-mercaptobenzothiazole to magnetic particles is 4:100.
[0022] By adopting the above technical solution, the present application strictly controls the weight ratio of 2-mercaptobenzothiazole and magnetic particles to 4:100, and maximizes the corrosion inhibition effect of the magnetic corrosion inhibition particles without incurring additional costs. Experimental data show that at this time, the corrosion potential of the topcoat coating is -0.047V and the friction coefficient is 0.355.
[0023] Preferably, the raw materials used also include mica nanosheets, and the weight ratio of the mica nanosheets to the magnetic corrosion-inhibiting particles is (0.2-1):1.
[0024] The preparation method of mica nanosheets is as follows: natural mica is calcined to remove impurities, then put into HNO3 solution, stirred, and then washed with water until the pH value of the supernatant is greater than 6, the obtained powder is dispersed in saturated NaCl solution, continuously stirred, membrane filtered, then dispersed with water, cetyltrimethylammonium bromide is added and stirred, filtered, washed, dispersed in ethanol, ultrasonically treated, centrifuged, and vacuum dried to obtain mica nanosheets.
[0025] By adopting the above technical solution, the present application adds a certain amount of mica nanosheets into the system, which have a dense layered structure and can form a stack of sheets in the system, extending the diffusion path of the corrosive medium in the topcoat coating, thereby reducing the possibility of the corrosive medium contacting the metal surface. Mica nanosheets can play a good synergistic role with magnetic corrosion inhibition particles, starting from strengthening active corrosion inhibition and strengthening passive barrier properties, greatly improving the corrosion resistance of the topcoat coating.
[0026] Preferably, the weight ratio of the mica nanosheets to the magnetic corrosion-inhibiting particles is 0.7:1.
[0027] By adopting the above technical scheme, the application strictly controls the amount of mica nanosheets added. Experimental data confirms that when the weight ratio of mica nanosheets to magnetic corrosion-inhibiting particles is 0.7:1, the corrosion resistance of the topcoat coating is the highest, the corrosion potential of the topcoat coating is -0.032V, and the friction coefficient is 0.355.
[0028] In a second aspect, the present application provides a method for preparing a composition coating for metal surfaces, comprising the following steps: uniformly mixing precured epoxy resin, PU-PI polymer, magnetic corrosion inhibition particles and an organic solvent to obtain a composition coating for metal surfaces.
[0029] In summary, this application has the following beneficial technical effects: 1. In the composite coating of the present application, the precured epoxy resin and the PU-PI polymer can be tightly linked in the system and form a strong interface bond with the metal surface, which greatly improves the adhesion and peeling resistance of the composite coating. The magnetic corrosion-inhibiting particles can further improve the corrosion resistance of the composite coating by virtue of their own ability to migrate directionally with the magnetic field and release corrosion-inhibiting substances. Therefore, the composite coating of the present application starts from improving the adhesion effect and corrosion resistance of the topcoat coating, and jointly protects the metal surface, so that the degree of corrosion in harsh environments is significantly reduced, and the service life of the metal surface is greatly extended; 2. The present application adds a certain amount of mica nanosheets to the system, which has a dense layered structure and can form a stack of sheets in the system, extending the diffusion path of the corrosive medium in the topcoat coating, thereby reducing the possibility of the corrosive medium contacting the metal surface. Mica nanosheets can play a good synergistic role with the magnetic corrosion-inhibiting particles, and start from strengthening the active corrosion inhibition and strengthening the passive barrier properties, greatly improving the corrosion resistance of the topcoat coating; 3. In the present application, MoS2 is loaded on the Fe3O4 nanoparticles in the magnetic corrosion inhibition particles. The two can form covalent bonds under the silane connection, which not only enhances the binding force between the magnetic corrosion inhibition particles and other components, but also increases the cross-linking density inside the topcoat coating, and reduces the possibility of corrosive substances diffusing into the topcoat coating / metal surface, thereby providing good corrosion protection for the metal surface. At the same time, it can also further enhance the wear resistance of the topcoat coating by virtue of the high mechanical stability of Fe3O4 nanoparticles and MoS2. DETAILED DESCRIPTION
[0030] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Epoxy resin was purchased from Hangzhou Wuhuigang Co., Ltd., model number JH-5539; The curing agent was purchased from Shandong Aite Chemical Co., Ltd., and its main component was polyethylene polyamine; Polybutylene glycol was purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd.; Hexamethylene diisocyanate was purchased from Aladdin Biochemical Technology Co., Ltd.; Dibutyltin dilaurate was purchased from Beijing Chemical Plant; N,N-Dimethylacetamide was purchased from Aladdin Biochemical Technology Co., Ltd.; Isophthalic acid dihydrazide was purchased from Beijing Chemical Plant; Diaminodiphenyl ether was purchased from Beijing Chemical Plant; Hexafluorodianhydride was purchased from Aladdin Biochemical Technology Co., Ltd.; Hexadecyltrimethylammonium bromide was purchased from Sane Chemical Technology (Shanghai) Co., Ltd.; Tetraethyl orthosilicate was purchased from Aladdin Biochemical Technology Co., Ltd.; 2-Mercaptobenzothiazole was purchased from Sane Chemical Technology (Shanghai) Co., Ltd.; MoS2 was purchased from Aladdin Biochemical Technology Co., Ltd.; Fe3O4 nanoparticles were purchased from Aladdin Biochemical Technology Co., Ltd. with a particle size of 20 nm; N,N-Dimethylformamide was purchased from Beijing Chemical Plant; Natural mica was purchased from Hebei Zhensheng Mining Co., Ltd. with a mesh size of 20 mesh.
[0031] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0032] Preparation Example 1 The preparation method of precured epoxy resin comprises the following steps: The epoxy resin and the curing agent were mixed in a weight ratio of 4:1, and pre-cured for 3 minutes at a temperature of 80° C. and a relative humidity of 45 RH% to obtain a pre-cured epoxy resin.
[0033] Preparation Example 2 The preparation method of PU-PI polymer comprises the following steps: 1. Heat polybutylene glycol to 80°C, add hexamethylene diisocyanate and dibutyltin dilaurate after it is completely melted, stir at 80°C for 3 hours to obtain HDI-PTMEG prepolymer, cool to room temperature, add anhydrous N,N-dimethylacetamide and isophthalic acid dihydrazide, continue stirring at room temperature for 2 hours to carry out chain extension reaction, and obtain PU solution, wherein the weight ratio of polybutylene glycol, hexamethylene diisocyanate, dibutyltin dilaurate, anhydrous N,N-dimethylacetamide and isophthalic acid dihydrazide is 8:0.48:0.0018:42.7:0.48; 2. Mix diaminodiphenyl ether and anhydrous N,N-dimethylacetamide, stir under a nitrogen atmosphere, and then add 0.165 g / mL of hexafluorodianhydride-anhydrous N,N-dimethylacetamide solution to obtain a PI solution, wherein the weight ratio of diaminodiphenyl ether, anhydrous N,N-dimethylacetamide and hexafluorodianhydride-anhydrous N,N-dimethylacetamide solution is 8.8:42.6:147.6; 3. After heating the PU solution to 80°C, add an equal volume of PI solution thereto, and continue to react at 80°C for 12 hours to obtain a PU-PI polymer.
[0034] Preparation Example 3.1 The preparation method of magnetic corrosion-inhibiting particles comprises the following steps: 1. Disperse 11kg of hexadecyltrimethylammonium bromide in 500L of ultrapure water, stir at 50°C for 2h, then add 3kg of Fe3O4 nanoparticles and 250L of ethylene glycol, stir continuously for 30min, then drop 300L of tetraethyl orthosilicate, react the resulting mixture at 100°C for 24h, then separate the precipitate by centrifugation, and rinse three times with deionized water to remove impurities. Finally, calcine the above precipitate at 550°C for 10h, wash the resulting solid dispersion and dry it in a vacuum oven at 80°C for 24h to obtain magnetic particles; 2. Disperse 120 g of 2-mercaptobenzothiazole in 60 L of acetone, then add 4 kg of the magnetic particles prepared in step I, adsorb at a pressure of 0.098 MPa for 8 h, then centrifuge at 8000 rpm for 5 min, wash with deionized water, and vacuum dry at 80°C overnight to obtain magnetic corrosion inhibition particles.
[0035] Preparation Example 3.2 The preparation method of magnetic corrosion-inhibiting particles comprises the following steps: 1. Disperse 1.1 kg of hexadecyltrimethylammonium bromide in 500 L of ultrapure water, stir at 50 ° C for 2 hours, then add 3 kg of Fe3O4 nanoparticles and 250 L of ethylene glycol, stir continuously for 30 minutes, then drop 30 L of tetraethyl orthosilicate, react the resulting mixture at 100 ° C for 24 hours, then separate the precipitate by centrifugation, and rinse three times with deionized water to remove impurities. Finally, calcine the above precipitate at 550 ° C for 10 hours, wash the resulting solid dispersion and dry it in a vacuum oven at 80 ° C for 24 hours to obtain magnetic particles; 2. Disperse 200 g of 2-mercaptobenzothiazole in 60 L of acetone, then add 4 kg of the magnetic particles prepared in step I, adsorb at a pressure of 0.098 MPa for 8 h, then centrifuge at 8000 rpm for 5 min, wash with deionized water, and vacuum dry at 80°C overnight to obtain magnetic corrosion inhibition particles.
[0036] Preparation Example 3.3 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 3.1 in that in step II, the amount of 2-mercaptobenzothiazole used is 160 g, and the rest is the same as that of Preparation Example 3.1.
[0037] Preparation Example 3.4 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 3.1 in that in step II, the amount of 2-mercaptobenzothiazole used is 100 g, and the rest is the same as that of Preparation Example 3.1.
[0038] Preparation Example 3.5 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 3.1 in that in step II, the amount of 2-mercaptobenzothiazole used is 250 g, and the rest is the same as that of Preparation Example 3.1.
[0039] Preparation Example 4.1 The preparation method of magnetic corrosion inhibition particles is different from that of Preparation Example 3.1 in that the Fe3O4 nanoparticles in step I are also subjected to MoS2 loading treatment, specifically: 1.2 kg of MoS2 was dispersed in 10 L of N,N-dimethylformamide and ultrasonically dispersed for 0.5 h to form a suspension. Subsequently, 3 kg of Fe3O4 nanoparticles were added to the suspension and ultrasonically dispersed for another 0.5 h. The mixture was stirred and reacted at 105 °C for 5 h. The mixture was then filtered, washed, and dried at 60 °C for 5 h to obtain MoS2-supported Fe3O4 nanoparticles.
[0040] Preparation Example 4.2 The preparation method of magnetic corrosion inhibition particles is different from that of Preparation Example 3.1 in that the Fe3O4 nanoparticles in step I are also subjected to MoS2 loading treatment, specifically: 3 kg of MoS2 was dispersed in 10 L of N,N-dimethylformamide and ultrasonically dispersed for 0.5 h to form a suspension. Subsequently, 3 kg of Fe3O4 nanoparticles were added to the suspension and ultrasonically dispersed for 0.5 h. The mixture was stirred and reacted at 105 °C for 5 h. The mixture was then filtered, washed, and dried at 60 °C for 5 h to obtain MoS2-loaded Fe3O4 nanoparticles.
[0041] Preparation Example 4.3 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 4.1 in that the amount of MoS2 used is 1.8 kg, and the rest is the same as Preparation Example 4.1.
[0042] Preparation Example 4.4 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 4.1 in that the amount of MoS2 used is 1 kg, and the rest is the same as Preparation Example 4.1.
[0043] Preparation Example 4.5 The preparation method of magnetic corrosion-inhibiting particles is different from that of Preparation Example 4.1 in that the amount of MoS2 used is 3.6 kg, and the rest is the same as Preparation Example 4.1.
[0044] Preparation Example 5 The method for preparing mica nanosheets comprises the following steps: 0.5 kg of natural mica was calcined at 800°C for 1 hour to remove impurities, then put into 2.5 L of 5.0 mol / L HNO3 solution and stirred at 95°C for 5 hours, then rinsed with water until the pH value of the supernatant was >6, the obtained powder was dispersed in 2.5 L of saturated NaCl solution, stirred continuously at 95°C for 3 hours, filtered through a 100 nm PTFE membrane, then dispersed with water, 125 g of hexadecyltrimethylammonium bromide was added and treated in a 300 W ultrasonic machine for 15 minutes, filtered, washed with deionized water, dispersed in 5 L of ethanol, and then the dispersion was centrifuged at 8000 rpm and vacuum dried for 12 hours to obtain mica nanosheets.
[0045] Comparative Preparation Example 1 The method for preparing magnetic particles comprises the following steps: 11kg of hexadecyltrimethylammonium bromide was dispersed in 500L of ultrapure water and stirred at 50°C for 2h, then 3kg of Fe3O4 nanoparticles and 250L of ethylene glycol were added thereto, and 300L of tetraethyl orthosilicate was added dropwise after continuous stirring for 30min. The resulting mixture was reacted at 100°C for 24h, and then the precipitate was separated by centrifugation and rinsed three times with deionized water to remove impurities. Finally, the above precipitate was calcined at 550°C for 10h, and the resulting solid was dispersed, washed and dried in a vacuum oven at 80°C for 24h to obtain magnetic particles.
[0046] Example 1.1 A method for preparing a composite coating for a metal surface comprises the following steps: The precured epoxy resin prepared in Preparation Example 1, the PU-PI polymer prepared in Preparation Example 2, the magnetic corrosion inhibition particles prepared in Preparation Example 3.1 and N,N-dimethylformamide were mixed evenly to obtain a composite coating for metal surfaces. The amount of each raw material is shown in Table 1.
[0047] Example 1.2 A method for preparing a composite coating for a metal surface comprises the following steps: The precured epoxy resin prepared in Preparation Example 1, the PU-PI polymer prepared in Preparation Example 2, the magnetic corrosion inhibition particles prepared in Preparation Example 3.2 and N,N-dimethylformamide were mixed evenly to obtain a composite coating for metal surfaces. The amount of each raw material is shown in Table 1.
[0048] Example 1.3 A method for preparing a composite coating for a metal surface comprises the following steps: The precured epoxy resin prepared in Preparation Example 1, the PU-PI polymer prepared in Preparation Example 2, the magnetic corrosion inhibition particles prepared in Preparation Example 3.1 and N,N-dimethylformamide were mixed evenly to obtain a composite coating for metal surfaces. The amount of each raw material is shown in Table 1.
[0049] Table 1 Amount of each raw material used in Examples 1.1-1.3 / kg Raw material name Example 1.1 Example 1.2 Example 1.3 Pre-cured epoxy resin 110 120 115 PU-PI polymer 25 20 23 Magnetic corrosion inhibition particles 0.5 1.5 1.0 N,N-Dimethylformamide 30 25 27 Examples 2.1-2.3 A method for preparing a composite coating for a metal surface, which is different from Example 1.1 in that the magnetic corrosion-inhibiting particles prepared in Preparation Example 3.1 are replaced by the magnetic corrosion-inhibiting particles prepared in Preparation Examples 3.3-3.5, respectively, and the rest is the same as Example 1.1.
[0050] Examples 3.1-3.2 A method for preparing a composite coating for a metal surface is different from Example 1.1 in that the magnetic corrosion-inhibiting particles prepared in Preparation Example 3.1 are replaced by the magnetic corrosion-inhibiting particles prepared in Preparation Examples 4.1-4.2, respectively, and the rest is the same as Example 1.1.
[0051] Examples 3.3-3.5 A method for preparing a composite coating for a metal surface, which is different from Example 3.1 in that the magnetic corrosion-inhibiting particles prepared in Preparation Example 4.1 are replaced by the magnetic corrosion-inhibiting particles prepared in Preparation Examples 4.3-4.5, respectively, and the rest is the same as Example 3.1.
[0052] Example 4.1 A method for preparing a composite coating for metal surfaces, which is different from Example 1.1 in that 0.1 kg of mica nanosheets prepared in Preparation Example 5 are also added, and the rest is the same as Example 1.1.
[0053] Example 4.2 A method for preparing a composite coating for metal surfaces, which is different from Example 1.1 in that 0.2 kg of mica nanosheets prepared in Preparation Example 5 are also added, and the rest is the same as Example 1.1.
[0054] Example 4.3 A method for preparing a composite coating for a metal surface, which is different from Example 1.1 in that 0.25 kg of mica nanosheets prepared in Preparation Example 5 are also added, and the rest is the same as Example 1.1.
[0055] Example 4.4 A method for preparing a composite coating for metal surfaces, which is different from Example 1.1 in that 0.35 kg of mica nanosheets prepared in Preparation Example 5 are also added, and the rest is the same as Example 1.1.
[0056] Example 4.5 A method for preparing a composite coating for metal surfaces, which is different from Example 1.1 in that 0.5 kg of mica nanosheets prepared in Preparation Example 5 are also added, and the rest is the same as Example 1.1.
[0057] Comparative Example 1 The difference from Example 1.1 is that the pre-cured epoxy resin prepared in Preparation Example 1 is replaced by epoxy resin, and 22 kg of curing agent is added, and the rest is the same as Example 1.1.
[0058] Comparative Example 2 The difference from Example 1.1 is that 25 kg of PU-PI polymer prepared in Preparation Example 2 is completely replaced by precured epoxy resin prepared in Preparation Example 1, and the rest is the same as Example 1.1.
[0059] Comparative Example 3.1 The difference from Example 1.1 is that the magnetic corrosion-inhibiting particles prepared in Preparation Example 3.1 are removed, and the rest are the same as Example 1.1.
[0060] Comparative Example 3.2 The difference from Example 1.1 is that the magnetic corrosion-inhibiting particles prepared in Preparation Example 3.1 are replaced by the magnetic particles prepared in Comparative Preparation Example 1, and the rest are the same as Example 1.1.
[0061] Performance Testing The composition coatings prepared in the examples and comparative examples were respectively sprayed on magnesium-aluminum alloy samples with a size of 200 mm×25 mm×6 mm to form a topcoat coating with a thickness of 50-65 μm on the metal surface to obtain test pieces. After the preparation, the following tests were performed: 1. Corrosion resistance: A cross scratch was made on the surface of the prepared topcoat coating, and the scratch was introduced deep into the metal substrate (2 cm long and 20 um wide) to ensure that the carbon steel was exposed to the corrosive medium. The sample was immersed in a 3.5 wt% NaCl solution for 24 h, and the electrochemical impedance spectroscopy (EIS) was performed on a three-electrode system electrochemical workstation to test its corrosion potential (V), wherein the working electrode and the reference electrode were platinum electrode and Hg / HgO electrode, respectively; 2. Adhesion ability: Refer to the method in Appendix G of SY / T0315-2013 to measure the adhesion of the topcoat coating on the sample. The immersion temperature in the pretreatment of the specimen is 70℃ and the immersion time is 28d. After taking out, while the specimen is still warm, use a knife to immediately scratch a rectangle of about 30mm×15mm on the coating, through the coating to reach the metal surface. After natural cooling for 1h, insert the tip of the knife under the coating from any corner of the rectangle, pry off the coating with horizontal force, and continue to push the tip of the knife until all the coating in the rectangle is pried off or the coating shows obvious anti-pry performance. The classification standard is: Level 1: The coating cannot be peeled off by prying; Level 2: The coating peeled off is less than or equal to 50%; Level 3: The coating is pried off by more than 50%, but the coating shows a certain degree of pry resistance; Level 4: The coating can be easily peeled off into strips or large pieces; Level 5: The coating is peeled off in one piece; 3. Wear resistance: The friction coefficient of the coating was tested using a reciprocating tribometer. The friction conditions were: the grinding material was a 6mm GCr15 bearing steel ball with a hardness of 60HRC. The experiment was carried out at room temperature and atmospheric environment. The normal load was 20N, the reciprocating speed was 100mm / min, and the test time was 30min.
[0062] Table 2 Performance test table Data Analysis: As can be seen from Table 2, the corrosion potential of Examples 1.1-1.3 is -0.058 to -0.052 V, the adhesion level is 1, and the friction coefficient is 0.351-0.356, which proves that in the composition coating of the present application, the precured epoxy resin and the PU-PI polymer can be tightly connected in the system and form a strong interface bond with the metal surface, which greatly improves the adhesion and peeling resistance of the composition coating. The magnetic corrosion-inhibiting particles can further improve the corrosion resistance of the composition coating by virtue of their own ability to migrate in a directional manner with the magnetic field and release corrosion-inhibiting substances. Therefore, the composition coating of the present application protects the metal surface from the two aspects of improving the adhesion effect and the anti-corrosion effect of the topcoat coating, so that the degree of corrosion in harsh environments is significantly reduced, and the service life of the metal surface is greatly extended; In Examples 2.1-2.3, the corrosion potential of Example 2.1 is significantly more positive than that of Example 1.1, and the friction coefficient is also better than that of Example 1.1, which proves that the present application achieves the best balance between the corrosion inhibition effect of the magnetic corrosion inhibition particles and the intuitive anti-corrosion effect and wear resistance of the topcoat coating by strictly controlling the weight ratio of MoS2 and Fe3O4 nanoparticles; The corrosion potential and friction coefficient of Examples 3.1-3.5 are better than those of Example 1.1, which proves that the present application not only enhances the binding force between the magnetic corrosion inhibition particles and other components, but also increases the crosslinking density inside the topcoat coating, and reduces the possibility of corrosive substances diffusing into the topcoat coating / metal surface, thereby providing good corrosion protection for the metal surface, but also can further enhance the wear resistance of the topcoat coating by virtue of the high mechanical stability of the Fe3O4 nanoparticles and MoS2; The corrosion potential and friction factor of Examples 4.1-4.5 are better than those of Example 1.1, proving that the present application adds a certain amount of mica nanosheets into the system, which have a dense layered structure and can form a stack of sheets in the system, extending the diffusion path of the corrosive medium in the topcoat coating, thereby reducing the possibility of the corrosive medium contacting the metal surface. Mica nanosheets can play a good synergistic role with magnetic corrosion inhibition particles, and start from both strengthening active corrosion inhibition and strengthening passive barrier properties, greatly improving the corrosion resistance of the topcoat coating; The corrosion potential of comparative example 1-2 is negative than that of example 1.1, the adhesion level is only level 2-3, and the friction coefficient is also higher than that of example 1.1, which proves that the present application uses a curing agent to pre-cure the epoxy resin under certain conditions, which can increase the number of active sites on the epoxy resin molecules, making it easier to combine with the PU-PI polymer having both a soft segment and a rigid segment, so that the PU-PI polymer is added to the system, and the mechanical stability and strong interface adhesion of the PU-PI polymer are used to improve the adhesion of the composition coating to the metal surface and its own corrosion resistance, and the system is tightly connected internally, so that the final topcoat coating can be permanently bonded to the metal surface and has a higher density; The corrosion potential of comparative examples 3.1-3.2 is more negative than that of example 1.1, and the friction coefficient is also higher than that of example 1.1, which proves that the magnetic corrosion inhibition particles of the present application can be evenly dispersed in the system without large-area agglomeration. During the spraying and curing process of the composition coating, the magnetic corrosion inhibition particles are affected by the magnetic field on the metal surface. The magnetic corrosion inhibition particles will migrate in a directed manner under the magnetic field and be enriched in the area near the metal surface. At this time, the MBT in the magnetic corrosion inhibition particles can move along the shortest path when the metal surface is corroded and quickly form a passivation layer at the corrosion site, which has a good protective effect on the metal surface.
[0063] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A composition coating for metal surface, characterized in that: The raw materials used include the following components in parts by weight: 110-120 parts of precured epoxy resin; 20-25 parts of PU-PI polymer; 0.5-1.5 parts of magnetic corrosion-inhibiting particles; and 25-30 parts of organic solvent.
2. The composition coating for metal surface according to claim 1, characterized in that: In parts by weight, the amount of the pre-cured epoxy resin is 115 parts, the amount of the PU-PI polymer is 23 parts, the amount of the magnetic corrosion-inhibiting particles is 1.0 parts, and the amount of the organic solvent is 27 parts.
3. The composition coating for metal surface according to claim 1, characterized in that: The method for preparing the magnetic corrosion-inhibiting particles comprises the following steps: Hexadecyltrimethylammonium bromide, Fe3O4 nanoparticles, ethylene glycol and tetraethyl orthosilicate are mixed and reacted to obtain a precipitate, and the precipitate is calcined, washed and dried to obtain magnetic particles; 2-Mercaptobenzothiazole and magnetic particles are mixed in a weight ratio of (3-5):100, adsorbed under reduced pressure, centrifuged, washed, and dried to obtain magnetic corrosion inhibition particles.
4. The composition coating for metal surface according to claim 3, characterized in that: The Fe3O4 nanoparticles in step I are also subjected to MoS2 loading treatment, specifically: MoS2 and Fe3O4 nanoparticles in a weight ratio of (0.4-1):1 are dispersed in DMF, stirred for reaction, filtered, washed, and dried to obtain MoS2-supported Fe3O4 nanoparticles.
5. The composition coating for metal surface according to claim 4, characterized in that: The weight ratio of the MoS2 to Fe3O4 nanoparticles is 0.6:
1.
6. The composition coating for metal surface according to claim 3, characterized in that: In the step II, the weight ratio of 2-mercaptobenzothiazole to the magnetic particles is 4:
100.
7. The composition coating for metal surface according to claim 1, characterized in that: The raw materials used also include mica nanosheets, and the weight ratio of the mica nanosheets to the magnetic corrosion-inhibiting particles is (0.2-1):
1.
8. The composition coating for metal surface according to claim 7, characterized in that: The weight ratio of the mica nanosheets to the magnetic corrosion-inhibiting particles is 0.7:
1.
9. A method for preparing a composition coating for metal surface according to any one of claims 1 to 8, characterized in that: The following steps are involved: The precured epoxy resin, PU-PI polymer, magnetic corrosion-inhibiting particles and organic solvent are uniformly mixed to obtain a composite coating for metal surfaces.
Citation Information
Patent Citations
An anticorrosion coating composition, an anticorrosion film and an anticorrosive article
CN102575115A
Preparation method of self-healing anti-corrosion coating based on magnetic gradient
CN107674548A
Synthetic method of magnetic mesoporous silica for removing copper ions in water
CN111437792A
Coating for diamond bag cage surface protection
CN114213940A
Modified nano Fe3O4-epoxy resin composite material and preparation method thereof
CN116769382A